(untitled) (Research, Society and Development, 2021)
The transition from face-to-face teaching to the emergency remote format during the pandemic affected teachers and students in a different way, at all levels of education and age groups, including institutional programs for teaching initiation scholarships such as PIBID, for example, that also had to adapt to this new reality. Given this perspective, a diagnostic analysis of the perception of remote teaching by undergraduate students at IFSULDEMINAS linked to the teaching initiation programs. Thus, from the activities carried out at the 6th Undergraduate Meeting, organized by IFSULDEMINAS, online, the answers were obtained from the application of a questionnaire with open questions on Google Forms and from the open reports in a debate held previously by Google Meet. It took 354 responses in which the absence of social interaction, lack of focus and interest in activities due to the amount of distractions, and practical classes are among the main aspects covered by the students. Meanwhile, the possibility of flexible schedule, learning new technologies and information about studying at home appear as the most cited positive aspects. There are, therefore, positive and negative impacts of remote teaching for higher education courses at IFSULDEMINAS, which developed actions in the search for methodologies and actions to help students. Porém, constata-se a necessidade de mais estudos para mensurar o impacto do ensino remoto, ocasionado pela pandemia, sobre o aprendizado. However, there is a need for more studies to measure the impact of remote teaching, caused by the pandemic, on learning.